Development of surface plasmon resonance sensor based on graphene quantum dots and cellulose-based biopolymers for phenol detection - Hashim, Hazwani Suhaila (2024)
The extensive discharge of phenol into aquatic environments from industrial sectors has led to adverse effects on living organisms due to its high toxicity. Hence, various detection methods have been developed, with surface plasmon resonance (SPR) standing out for its label-free analysis and real-time detection. However, this sensor struggles with poor sensitivity to low concentrations of target analytes. In this regard, SPR sensor has been integrated with graphene quantum dots (GQDs), sodium carboxymethyl cellulose (NaCMC), nanocrystalline cellulose (NCC), NaCMC-GQDs, and NCC-GQDs thin films for phenol detection, for the first time. The structural properties of the NaCMC-GQDs and NCC-GQDs thin films, determined using Fourier transform infrared spectroscopy and atomic force microscopy, confirmed the presence of O–H, C–H, C=O, and C=C stretching, as well as C–H bending, with an additional C–O stretching peak for NaCMC-GQDs, and showed that the surfaces of the thin films were covered with NaCMC and NCC, respectively. Moreover, the optical properties, examined using ultraviolet-visible spectroscopy, revealed energy band gap values of 4.088 eV and 4.094 eV for the NaCMC-GQDs and NCC-GQDs thin films, respectively. The sensing performance of the thin films coated with sensing materials (GQDs, NaCMC, NCC, NaCMC-GQDs, and NCC-GQDs) for phenol detection was analyzed using the SPR sensor. Limits of detection (LOD) of 0.1 μM for GQDs, 0.01 fM for NaCMC and NCC, and 0.001 fM for NaCMC-GQDs and NCC-GQDs were achieved, outperforming the gold thin film with a LOD of 1 μM. This can be attributed to phenol binding to the sensing materials through hydrogen bonds, π-π stacking interactions, and carbohydrate-aromatic interactions. Among all the thin films, the NCC-GQDs thin film showed the best sensing performance with the lowest LOD of 0.001 fM and a sensitivity of 0.02038° M-1, surpassing the NaCMC-GQDs thin film's sensitivity of 0.01353° M-1 with the same LOD value. Integration with tyrosinase (Tyr) enzyme further enhanced its sensitivity to 0.04657° M-1. The NCC-GQDs-Tyr thin film showed outstanding selectivity for phenol, evidenced by significant resonance angle shifts for the mixtures of interferents containing phenol compared to those without. The sensor also demonstrated good stability over a 14-day storage period and excellent recovery rates for detecting phenol in spiked water samples. The NCCGQDs- Tyr thin film incorporated SPR sensor has shown great potential as a reliable tool for sensitive and selective phenol detection.